Audit Quality Differences Based on KAP Size and Auditor Switching: Perbedaan Kualitas Audit Berdasarkan Ukuran KAP dan Pergantian Auditor - Yuniati, Mochammad David Hardiansyah; Sari, Rida Perwita (Universitas Muhammadiyah Sidoarjo, 2025)
Audit quality plays a critical role in ensuring corporate transparency and accountability amid growing stakeholder scrutiny. Specifically, the role of Public Accounting Firm (KAP) size and mandatory auditor switching regulations has been widely debated in Indonesia following financial scandals and regulatory shifts. However, empirical findings on the mediating role of auditor switching between KAP size and audit quality remain inconclusive, especially in the transportation and logistics sector. This study aims to examine the direct and mediated effects of KAP size on audit quality through auditor switching using data from 23 IDX-listed companies (2020–2023), analyzed via PLS-SEM with WarpPLS 8.0. Results reveal that while KAP size significantly influences audit quality and auditor switching decisions, auditor switching alone does not significantly affect audit quality, nor does it mediate the main relationship. The novelty of this research lies in its sector-specific context, post-pandemic timeline, and robust modeling technique, providing clarity in an underexplored domain. Implications suggest that policymakers should reassess the effectiveness of auditor switching mandates, while companies are advised to prioritize KAP size and reputation over mandatory rotation in pursuit of audit quality.Highlight : Firm Size Matters – Large (Big Four) accounting firms are statistically proven to improve audit quality directly. Switching Not Always Effective – Auditor switching alone does not significantly enhance audit quality. No Mediation Found – Auditor switching does not mediate the relationship between firm size and audit quality. Keywords : Auditor Switching, Audit Quality, KAP Size, Big Four, PLS-SEM